ChemInform Abstract: A Reagent for Safe and Efficient Diazo‐Transfer to Primary Amines: 2‐Azido‐1, 3‐dimethylimidazolinium Hexafluorophosphate. Issue 48 (2nd December 2014) - Kitamura, Mitsuru; Kato, So; Yano, Masakazu; Tashiro, Norifumi; Shiratake, Yuichiro; Sando, Mitsuyoshi; Okauchi, Tatsuo
Abstract The title compound, a safe, crystalline, and commercially available substance, is found to be an efficient diazo‐transfer reagent for primary amines, even without the aid of a metal salt such as Cu(II).